A Knowledge based Programme for Decision Support in Steel Manufacturing Industries - Deepak Sharma (International Journal of Advanced Science and Technology, 2020)
Knowledge-based Systems (KBS) is a framework utilizing knowledge-based approaches to assist human decision-making, understanding and practice. These systems are expected to communicate with human users, but the nature of the assistance provided and the manner in which it is delivered are essential issues.Decision Support Systems (DSS) is a particular type of information system that facilitates the development of cost effective quality product designs, business decision-making and operational activities. Implementing a decision support program at a steel plant is a daunting job. There are several functional areas viz marketing, supply chain, product planning, finance and production which are required to take several critical decisions. When the knowledge based system is embedded into a decision support system and applied to steel industries several benefits can be reaped. This paper discusses the structure of KBS and DSS in detail. One segment of the article is completely dedicated to implementation of knowledge based decision support system (KBDSS) in steel industries. The article concludes with the summary of benefits and pitfalls of KBDSS implementation.